On the development of lift and drag in a rotating and translating cylinder - Martín-Alcántara, Antonio; Sanmiguel-Rojas, Enrique; Fernández-Feria, Ramón (Elsevier, 2015)
The two-dimensional flow around a rotating cylinder is investigated nu- merically using a vorticity forces formulation with the aim of analyzing quan- titatively the flow structures, and their evolutions, that contribute to the lift and drag forces on the cylinder. The Reynolds number considered, based on the cylinder diameter and steady free stream speed, is Re = 200, while the non-dimensional rotation rate (ratio of the surface speed and free stream speed) selected were α = 1 and 3. For α = 1 the wake behind the cylinder for the fully developed flow is oscillatory due to vortex shedding, and so are the lift and drag forces. For α = 3 the fully developed flow is steady with constant (high) lift and (low) drag. Each of these cases is considered in two different transient problems, one with angular acceleration of the cylinder and constant speed, and the other one with translating acceleration of the cylinder and constant rotation. We characterize quantitatively the contribu- tions of individual fluid elements (vortices) to aerodynamic forces, explaining and quantifying the mechanisms by which the lift is generated in each case. In particular, for high rotation (when α = 3), we explain the relation between the mechanisms of vortex shedding suppression and those by which the lift is enhanced and the drag is almost suppressed when the fully developed flow is reached.
Keywords: Aerodinámica; Mecánica de Fluidos